Kinetics and 28-day test–retest repeatability and reproducibility of [11C]UCB-J PET brain imaging. Issue 6 (June 2021) - Tuncel, Hayel; Boellaard, Ronald; Coomans, Emma M; de Vries, Erik FJ; Glaudemans, Andor WJM; Feltes, Paula Kopschina; García, David V; Verfaillie, Sander CJ; Wolters, Emma E; Sweeney, Steven P; Ryan, J Michael; Ivarsson, Magnus; et al.
[ 11 C]UCB-J is a novel radioligand that binds to synaptic vesicle glycoprotein 2A (SV2A). The main objective of this study was to determine the 28-day test–retest repeatability (TRT) of quantitative [ 11 C]UCB-J brain positron emission tomography (PET) imaging in Alzheimer's disease (AD) patients and healthy controls (HCs). Nine HCs and eight AD patients underwent two 60 min dynamic [ 11 C]UCB-J PET scans with arterial sampling with an interval of 28 days. The optimal tracer kinetic model was assessed using the Akaike criteria (AIC). Micro-/macro-parameters such as tracer delivery (K1 ) and volume of distribution (VT ) were estimated using the optimal model. Data were also analysed for simplified reference tissue model (SRTM) with centrum semi-ovale (white matter) as reference region. Based on AIC, both 1T2k_VB and 2T4k_VB described the [ 11 C]UCB-J kinetics equally well. Analysis showed that whole-brain grey matter TRT for VT, DVR and SRTM BPND were –2.2% ± 8.5, 0.4% ± 12.0 and –8.0% ± 10.2, averaged over all subjects. [ 11 C]UCB-J kinetics can be well described by a 1T2k_VB model, and a 60 min scan duration was sufficient to obtain reliable estimates for both plasma input and reference tissue models. TRT for VT, DVR and BPND was <15% (1SD) averaged over all subjects and indicates adequate quantitative repeatability of [ 11 C]UCB-J PET.